2020
DOI: 10.3390/molecules25061472
|View full text |Cite
|
Sign up to set email alerts
|

Photocrosslinking of cDNA Display Molecules with Their Target Proteins as a New Strategy for Peptide Selection

Abstract: Binding peptides for given target molecules are often selected in vitro during drug discovery and chemical biology research. Among several display technologies for this purpose, complementary DNA (cDNA) display (a covalent complex of a peptide and its encoding cDNA linked via a specially designed puromycin-conjugated DNA) is unique in terms of library size, chemical stability, and flexibility of modification. However, selection of cDNA display libraries often suffers from false positives derived from non-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Furthermore, little non‐specific crosslinking was observed in these DPAL methods, attributed to crosslinking being proportional to ligand affinity towards the target, [163] (a high effective molarity is present for the photo‐crosslinker only in cases of binding). A similar idea has been demonstrated for mRNA‐displayed peptides (using the cDNA display approach) where a photo‐crosslink is formed between a short oligonucleotide on the target protein and a complementary sequence introduced into the puromycin linker (similar to site 4 in section 4.2 above, although not at the extreme 3’ end) [17] . This has not yet been used to enrich target binders, but clearly demonstrates the feasibility of using other crosslinker‐based approaches in mRNA display.…”
Section: Selection Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…Furthermore, little non‐specific crosslinking was observed in these DPAL methods, attributed to crosslinking being proportional to ligand affinity towards the target, [163] (a high effective molarity is present for the photo‐crosslinker only in cases of binding). A similar idea has been demonstrated for mRNA‐displayed peptides (using the cDNA display approach) where a photo‐crosslink is formed between a short oligonucleotide on the target protein and a complementary sequence introduced into the puromycin linker (similar to site 4 in section 4.2 above, although not at the extreme 3’ end) [17] . This has not yet been used to enrich target binders, but clearly demonstrates the feasibility of using other crosslinker‐based approaches in mRNA display.…”
Section: Selection Methodsmentioning
confidence: 89%
“…In the same variant, shifting the puromycin from the 3’ end to a branched chain of a modified nucleobase in the linker also allows the same oligonucleotide to be used as the reverse transcription primer and thus encode the peptide information directly in DNA that is covalently attached to the peptide (termed ‘cDNA display’ by the authors) [16] . Photo‐crosslinking simplifies purification of the resulting product, but care needs to be taken with the 365 nm light used to activate the psoralen to avoid damage to the nucleic acids (photocrosslinked mRNA display) [17] . Finally, annealing alone gives a sufficiently stable connection if the complementary sequence is long enough and this allows a much faster protocol (termed ‘TRAP display’ by the authors) [18] .…”
Section: Variants Of Mrna Display and Dna‐encoded Librariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, p50-DNA binding leads to target capture, and the conjugate could be purified for hit decoding. Recently, Nemoto and co-workers reported a similar method for the selection of cDNA-display libraries …”
Section: Discussionmentioning
confidence: 99%
“…Recently, Nemoto and co-workers reported a similar method for the selection of cDNA-display libraries. 38 DELs could be encoded with double-or single-stranded DNA (dsDNA or ssDNA) tags. Although a recent study showed that ssDNA-DELs gave better enrichment, 39 most DELs are still built with dsDNAs, presumably because of the higher chemical stability of dsDNA.…”
Section: Applying Dpal In Del Selectionsmentioning
confidence: 99%